2014
DOI: 10.1007/s11420-014-9392-x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesia with Saphenous Block Appears Equivalent to Femoral Nerve Block in ACL Reconstruction

Abstract: Background: Adequate pain control following anterior cruciate ligament reconstruction (ACL) often requires regional nerve block. The femoral nerve block (FNB) has been traditionally employed. Ultrasound application to regional nerve blocks allows for the use of alternatives such as the saphenous nerve block following ACL reconstruction. Questions/Purposes: This study evaluated postoperative analgesia provided by the subsartorial saphenous nerve block (SSNB) compared to that provided by the traditional FNB for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 21 publications
6
62
0
Order By: Relevance
“…In contrast, a recent study showed that both blocks had comparable postoperative analgesia after ACLR. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a recent study showed that both blocks had comparable postoperative analgesia after ACLR. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [4] demonstrated that the subsartorial saphenous nerve block (SSNB) was as efficacious as the traditional femoral nerve block (FNB) [9,18] for postoperative analgesia following bone-tendon-bone (BTB)-anterior cruciate ligament (ACL) reconstruction. With the efficacy of SSNB having been established, this study investigates whether analgesia could be extended by the addition of preservative-free dexamethasone.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have found good pain control with infrapatellar nerve blockade as part of a multimodal perioperative analgesia approach, 45 while other evidence suggests that saphenous block may be sufficient in ACL reconstruction with patellar graft. 46 However, the causality between falls and muscle weakness during or following a nerve block in the setting of major knee surgery remains an area of debate. There is little evidence to suggest that regional anesthesia has an impact on functionality following ACL beyond the early postoperative period.…”
Section: Evidence and Outcomesmentioning
confidence: 99%